2017
DOI: 10.1016/j.euroneuro.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

A positron emission tomography study of the serotonergic system in relation to anxiety in depression

Abstract: Symptoms of anxiety are highly comorbid with major depressive disorder (MDD) and are known to alter the course of the disease. To help elucidate the biological underpinnings of these prevalent disorders, we previously examined the relationship between components of anxiety (somatic, psychic and motoric) and serotonin 1A receptor (5-HT1A) binding in MDD and found that higher psychic and lower somatic anxiety was associated with greater 5-HT1A binding. In this work, we sought to examine the correlation between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Raw list-mode PET data was reconstructed offline using Siemens’ e7 Tools software and a CT-like MR-based attenuation map ( Izquierdo-Garcia et al., 2014 , Ladefoged et al., 2017 ). Motion correction and PET-to-MRI coregistration were done before time activity curves were generated as previously described ( Iscan et al., 2017 ). To obtain a quantitative measure of [ 18 F]-FEPPA uptake, two-tissue-compartmental (2 ​TC) kinetic modeling was performed to quantify the total distribution volume ( V T ) as the outcome measure, as previously validated ( Rusjan et al., 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…Raw list-mode PET data was reconstructed offline using Siemens’ e7 Tools software and a CT-like MR-based attenuation map ( Izquierdo-Garcia et al., 2014 , Ladefoged et al., 2017 ). Motion correction and PET-to-MRI coregistration were done before time activity curves were generated as previously described ( Iscan et al., 2017 ). To obtain a quantitative measure of [ 18 F]-FEPPA uptake, two-tissue-compartmental (2 ​TC) kinetic modeling was performed to quantify the total distribution volume ( V T ) as the outcome measure, as previously validated ( Rusjan et al., 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…One study found that low SERT binding in thalamus was correlated with higher anxiety symptoms in a small sample of ten unmedicated patients with MDD [11] which was later replicated (n = 10) [12]. Another group confirmed a negative correlation between somatic anxiety and SERT binding in the thalamus, midbrain and amygdala, while psychic anxiety was positively correlated with midbrain SERT binding [10].…”
Section: Introductionmentioning
confidence: 89%
“…The underlying mechanisms are not fully understood, but serotonin (5-HT) is assumed to play a key role and serotonergic-acting drugs are firstline pharmacotherapeutic options for treatment of both depression and anxiety disorders. Previous positron emission tomography (PET) studies of the serotonin system in patients with concurrent anxious depression are scarce and have mainly focused on the serotonin transporter (SERT) and the 5-HT 1A receptor [10,11]. One study found that low SERT binding in thalamus was correlated with higher anxiety symptoms in a small sample of ten unmedicated patients with MDD [11] which was later replicated (n = 10) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Urine-based metabolites involved in metabolic pathways were deemed as a hopeful diagnostic method for patients with depression and anxiety disorders 25 . Nevertheless, existing biomarkers in cerebrospinal fluid (CSF) [e.g., monoamine and cocaine- and amphetamine-regulated transcript (CART) peptide identify biomarkers for psychiatric diagnosis] 26 or positron emission tomography (PET) imaging [targeting serotonin transporter (5-HTT), 5-HTT and 5-HT1A, tau, neurofilament light, and neurogranin] 27 29 are invasive or expensive, far from comprehensive, and often lack sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%